Learning about Teaching - Kaebnick, Gregory E. (The Hastings Center report, 2014)
There are three broad themes in this issue of the Hastings Center Report. First, a special report published as a supplement to the issue addresses the medical and health policy issues faced by lesbian, gay, bisexual, and transgender patients. Inside the issue, the two articles take up questions about how caregivers may justify a refusal to provide a medical service that a patient has requested. The issue also contains a set of essays that have emerged from a collaborative effort by The Hastings Center and the Presidential Commission for the Study of Bioethical Issues to promote scholarly engagement with the practical problem of teaching caregivers, researchers, scientists, and others to address bioethical problems. What appears here is the first installment of a series that will appear in the pages of the Report well into the 2015 volume.